Enhancing Philosophical Concept Acquisition Through The 5E Learning Cycle Model - Ismael Ibrahim Ahmed (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
This quasi-experimental study investigated the effectiveness of the 5E Learning Cycle Model (Engage, Explore, Explain, Elaborate, Evaluate) in enhancing philosophical concept acquisition among eleventh-grade students in the Kurdistan Region of Iraq. Seventy-two male students from Sêmêl Preparatory School for Boys participated during the 2024–2025 academic year. Two intact eleventh-grade sections were randomly assigned to conditions, with the experimental group (n = 38) receiving instruction structured according to the five phases of the 5E model and the control group (n = 34) taught using conventional, textbook-centered methods. Instructional content covered three chapters from the Grade 11 Philosophy textbook: Introduction to Philosophy, Logic and Critical Thinking, and Ethics and Moral Philosophy. A 30-item philosophical concept acquisition test assessing definition, discrimination, and application levels (Kuder-Richardson 20 reliability = .83) was administered as both pre-test and post-test. Independent samples t-test revealed statistically significant differences (p < .05) favoring the experimental group in post-test performance (t = 7.214, df = 70). A paired samples t-test confirmed substantial within-group improvement in the experimental group (t = 18.936, df = 37). Large effect sizes (Cohen’s d = 1.71 and d = 4.07) underscore the practical significance of these findings, although the magnitude of these effects should be interpreted in light of the single-site sample, the relatively small group sizes, and the nine-week intervention duration. These results support the integration of the 5E Learning Cycle Model into secondary philosophy curricula and highlight the need for professional development programs that equip teachers with constructivist pedagogical skills. A key limitation is the single-school, all-male sample and the nine-week intervention period, which constrain generalizability and preclude assessment of long-term retention. The study’s novelty lies in extending the 5E model—previously examined mainly within science and mathematics education—into philosophy instruction within a Kurdish secondary school context, an area in which empirical evidence has thus far been absent.